Measuring cost efficiency in the Nordic Hospitals—a cross-sectional comparison of public hospitals in 2002 - Linna, Miika (Springer US, 2010)
The aim of this study was to compare the performance of hospital care in four Nordic countries: Norway, Finland, Sweden and Denmark. Using national discharge registries and cost data from hospitals, cost efficiency in the production of somatic hospital care was calculated for public hospitals. Data were collected using harmonised definitions of inputs and outputs for 184 hospitals and data envelopment analysis was used to calculate Farrell efficiency estimates for the year 2002. Results suggest that there were marked differences in the average hospital efficiency between Nordic countries. In 2002, average efficiency was markedly higher in Finland compared to Norway and Sweden. This study found differences in cost efficiency that cannot be explained by input prices or differences in coding practices. More analysis is needed to reveal the causes of large efficiency disparities between Nordic hospitals.